Exploring the antifungal potential of Cannabis sativa-derived stilbenoids and cannabinoids against novel targets through in silico protein interaction profiling - Kırboğa, Kevser Kübra; Karim, Aman; Küçüksille, Ecir Uğur; Rudrapal, Mithun; Khan, Johra; Achar, Raghu Ram; Silina, Ekaterina; Manturova, Natalia; Stupin, Victor (Frontiers in Chemistry, 2025)
Cannabinoid and stilbenoid compounds derived from Cannabis sativa were screened against eight specific fungal protein targets to identify potential antifungal agents. The proteins investigated included Glycosylphosphatidylinositol (GPI), Enolase, Mannitol-2-dehydrogenase, GMP synthase, Dihydroorotate dehydrogenase (DHODH), Heat shock protein 90 homolog (Hsp90), Chitin Synthase 2 (CaChs2), and Mannitol-1-phosphate 5-dehydrogenase (M1P5DH), all of which play crucial roles in fungal survival and pathogenicity. This research evaluates the binding affinities and interaction profiles of selected cannabinoids and stilbenoids with these eight proteins using molecular docking and molecular dynamics simulations. The ligands with the highest binding affinities were identified, and their pharmacokinetic profiles were analyzed using ADMET analysis. The results indicate that GMP synthase exhibited the highest binding affinity with Cannabistilbene I (−9.1 kcal/mol), suggesting hydrophobic solid interactions and multiple hydrogen bonds. Similarly, Chitin Synthase 2 demonstrated significant binding with Cannabistilbene I (−9.1 kcal/mol). In contrast, ligands such as Cannabinolic acid and 8-hydroxycannabinolic acid exhibited moderate binding affinities, underscoring the variability in interaction strengths among different proteins. Despite promising in silico results, experimental validation is necessary to confirm therapeutic potential. This research lays a crucial foundation for future studies, emphasizing the importance of evaluating binding affinities, pharmacokinetic properties, and multi-target interactions to identify promising antifungal agents.